Impact of Digital Marketing in Entrepreneurship: A Case of Kathmandu Valley - Chaudhary, Om Prakash; Pradhan, Radhe Shyam (Nepalese Journal of Management, 2025)
This study examines the impact of digital marketing in entrepreneurship. Competitiveness of entrepreneurship is the dependent variable. The selected independent variables are content marketing, mobile marketing, online advertising, email marketing and viral marketing. The primary sources of data is used to assess the opinions of respondents regarding content marketing, mobile marketing, online advertising, email marketing viral marketing and competitiveness of entrepreneurship. The study is based on the primary data of 125 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of impact of digital marketing in entrepreneurship: A case of Kathmandu Valley. The study showed a positive impact of content marketing on competitiveness of entrepreneurship. It indicates that businesses engaging in impactive content marketing strategies are better positioned to attract their target audience. Similarly, the study showed a positive impact of email marketing on competitiveness of entrepreneurship. It indicates that using impactive email marketing strategies may experience increased competitiveness through conversion rates. Likewise, the study showed a positive impact of online advertising on competitiveness of entrepreneurship. It indicates that strong online presences contribute to business competitiveness by reaching wider audience. In addition, the study also showed a positive impact of mobile marketing on competitiveness of entrepreneurship. It indicates that the entrepreneurs may see improvements in customer engagement and brand visibility contributing to more competitive position in the business landscape. Further, the study showed a positive impact of viral marketing on competitiveness of entrepreneurship. It indicates that spreading a message or product through digital networks can contribute to a business’s success in competitive market.